Meisterschule. : Claus Brunsmann - Brigitte Dams - Bärbel Schulte Kellinghaus - Ursula Habermacher - Christiane Löhr - Sandra Voets - Meneguzzo, Marco; Vettese, Angela; Galleria Salvatore + Caroline Ala, Milano (Milano : Edizioni Charta, 1998)
Six young artists, students attending Jannis Kounellis' course at the Düsseldorf Academy, have found a common denominator and shared attitudes and themes, whilst following their own personal paths, by exploring reality simply, but with awareness and seriousness and by turningtheir attention to the original problems of the world. Abstract painting, rubber, wood, glass, photographs of human bodies, human bodies in ronze, wax, plaster, thistle seeds, burdocks, sensual allusive flowers, and hundreds of frozen flowers for an art that these six artists intend to be "necessary" rather than "beautiful"
biog. p. 22, 26, 30, 34, 38, 42
Italiaans & Engels
Meisterschule, Galleria Salvatore + Caroline Ala, Milano, 19 December 1997 - 28 February 1998
boek
Keywords: Brunsmann, Claus; Dams, Brigitte; Schulte Kellinghaus, Bärbel; Habermacher, Ursula; Löhr, Christiane; Voets, Sandra